Case Report: Cardiac Multiple Thrombus and Pulmonary Embolism Associated With Mycoplasma Pneumonia Infection in a Child - Zhang, Tongqiang; Zheng, Jiafeng; Wang, Hongbo; Xu, Yongsheng; Ning, Jing; Cai, Chunquan (Frontiers in Pediatrics, 2022)
Mycoplasma pneumoniae (MP) is a common pathogen of lower respiratory tract infection in children and adolescents. Some patient with MP infection is self-limiting, while with the increase of severe or refractory Mycoplasma pneumoniae pneumonia (MPP) in recent years, there are an great increase in reports of thromboembolism in multiple organs, including lung, brain, spleen and peripheral arteries. Cardiac multiple thrombus and pulmonary embolism associated with MP infection have not been reported. The most effective treatment options for cardiac thrombus was surgical resection for fear of thrombus detachment and caused new thromboembolism. Herein, we present a patient with cardiac multiple thrombus and pulmonary embolism in MPP for the first time. In our case, the child recovered after conservative medical treatment, which provides a therapeutic option for children with cardiac multiple thrombus.